2011
DOI: 10.1111/j.1528-1167.2011.03270.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ventricular late potentials in signal-averaged ECG of people with epilepsy

Abstract: Summary Purpose:  There has been growing interest in cardiac disturbances in epilepsy patients and their etiologic role in the context of sudden death. Ventricular late potentials (VLPs) recorded on signal‐averaged electrocardiography (SAECG) reflects delayed ventricular depolarization and identifies the structural or functional substrate for the ventricular tachycardia in the reentry mechanism. Therefore, abnormal SAECG poses the potential of identifying patients at increased risk of malignant ventricular arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 32 publications
0
17
2
1
Order By: Relevance
“…Interestingly, the lack of VLPs after the initiation of AED therapy in our cohort of newly diagnosed epilepsy differs substantially from the findings by Rejdak et al [18] in a cohort with chronic epilepsy in which a VLP was present in 48% of the patients. In that study, VLPs were associated with polytherapy, high seizure frequency, and a long duration of epilepsy.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Interestingly, the lack of VLPs after the initiation of AED therapy in our cohort of newly diagnosed epilepsy differs substantially from the findings by Rejdak et al [18] in a cohort with chronic epilepsy in which a VLP was present in 48% of the patients. In that study, VLPs were associated with polytherapy, high seizure frequency, and a long duration of epilepsy.…”
Section: Discussioncontrasting
confidence: 83%
“…The deceased may previously have been asymptomatic [17] or have experienced recurrent syncopes [16]. Recently, VLPs were found to occur in 48% of a cohort with chronic epilepsy [18], and were correlated with long duration of epilepsy, frequent seizures, and polytherapy, of which all are well-known risk factors for SUDEP [4]. However, that study had insufficient power to evaluate whether the VLPs were associated with a particular AED.…”
Section: Introductionmentioning
confidence: 97%
“…QT and QTc dispersion are increased in epileptics this being independent of medication [57,58]. Nearly 50% of epileptics may have late potentials, unrelated to cardiac history or electrolyte imbalance a possible reflection of seizure-induced changes in cardiac ionic channels (see below) [59]. T wave alternans and asymptomatic ST segment depression during partial seizures have been described [60,61].…”
Section: Epilepsymentioning
confidence: 99%
“…Epilepsy patients more frequently displayed abnormal SAECGs with LVPs compared to healthy controls, correlated with disease duration, uncontrolled seizures, and polytherapy [23]. Svalheim et al [31] reported no electrocardiographic changes (in standard ECG and SAECG) after antiepileptic drugs (carbamazepine and lamotrigene) in 26 epileptic patients.…”
Section: Follow Up Referencesmentioning
confidence: 99%
“…The association between LVPs and rejection of heart transplant is explained by occurrence of areas of myocardial ibrosis, due to cell changes caused by alloreactive T lymphocytes against graft antigens and ischemia-reperfusion injuries as soon as the blood low is reestablished [22]. 20 young heart transplant patients SAECG is not efective in detecting heart transplant rejection in young patients Horenstein et al [21] Extracardiac disorders were also associated with LVPs, especially hypertension, metabolic syndrome, obesity, eating disorders, diabetes mellitus, renal failure, chronic obstructive pulmonary disease (COPD), acromegaly, thalassemia, connective tissue diseases, epilepsy, and schizophrenia [6,[23][24][25][26][27]. Antiarrhythmic therapy, thrombolytic drugs, statins, steroids, and coronary interventions may inluence LVPs [6].…”
Section: Late Ventricular Potentialsmentioning
confidence: 99%